2011
DOI: 10.1007/s00192-010-1357-0
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic vesical instillations with 0.2% chondroitin sulfate may reduce symptoms of acute radiation cystitis in patients undergoing radiotherapy for gynecological malignancies

Abstract: Introduction and hypothesisWe studied the feasibility and efficacy of intravesical instillations with 40 ml chondroitin sulfate 0.2% solution to prevent or reduce acute radiation cystitis in women undergoing pelvic radiotherapy.MethodsIn a comparative pilot study in 20 patients, half of the patients received instillations. Instillations' bother was measured with visual analog scores (VAS, 0–10); bladder pain, with VAS; micturition-related quality of life, with the urogenital distress inventory (UDI).ResultsOne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 14 publications
1
26
0
1
Order By: Relevance
“…The majority of the selected publications referred to BPS/ IC therapy, except for 2 papers on ChS 0.2 %, which evaluated the product in patients with overactive bladder [25,26] and for the prophylaxis of radiation cystitis [27]; 2 of the excluded articles reported on the efficacy of a combination of heparin and lidocaine as an acute analgesic intervention for severe pain [28,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the selected publications referred to BPS/ IC therapy, except for 2 papers on ChS 0.2 %, which evaluated the product in patients with overactive bladder [25,26] and for the prophylaxis of radiation cystitis [27]; 2 of the excluded articles reported on the efficacy of a combination of heparin and lidocaine as an acute analgesic intervention for severe pain [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that ChS is superior to other intravesical GAG substitutes. However, in their review, 368 patients who were treated with ChS had a diagnosis of OAB, 20 patients a diagnosis of radiation cystitis [27], and only 118 patients were Bexclusively^diagnosed with BPS/IC. The authors also state that no significant superiority versus controls was observed in the single controlled study on ChS 2 % that was reviewed [35].…”
Section: Discussionmentioning
confidence: 99%
“…Chondroitin sulfate has been validated in interstitial cystitis patients [50], and in a pilot study [51] to prevent radiation cystitis. Twenty patients with endometrial or cervical cancers were included in the study-ten were treated with 40 mL of 0.2 % solution of chondroitin sulfate weekly instillations and ten in the control group received no treatment.…”
Section: Other Agentsmentioning
confidence: 99%
“…A comparative pilot study in 20 patients planned for primary or adjuvant radiotherapy for endometrial or cervical cancer examined the feasibility and efficacy of intravesical instillations with 40 mL chondroitin sulfate (0.2%) solution in preventing or reducing acute radiation cystitis . Ten patients consented for weekly bladder instillations for the duration of radiation therapy while the remaining 10 did not opt for intravesical treatment and served as controls.…”
Section: Experimental Modalitiesmentioning
confidence: 99%